Regional variation of potentially avoidable hospitalisations in Switzerland: an observational study - Niklaus Gygli; Franziska Zúñiga; Michael Simon (BMC, 2021)
Abstract Background Primary health care is subject to regional variation, which may be due to unequal and inefficient distribution of services. One key measure of such variation are potentially avoidable hospitalisations, i.e., hospitalisations for conditions that could have been dealt with in situ by sufficient primary health care provision. Particularly, potentially avoidable hospitalisations for ambulatory care-sensitive conditions (ACSCs) are a substantial and growing burden for health care systems that require targeting in health care policy. Aims Using data from the Swiss Federal Statistical Office (SFSO) from 2017, we applied small area analysis to visualize regional variation to comprehensively map potentially avoidable hospitalisations for five ACSCs from Swiss nursing homes, home care organisations and the general population. Methods This retrospective observational study used data on all Swiss hospitalisations in 2017 to assess regional variations of potentially avoidable hospitalisations for angina pectoris, congestive heart failure, chronic obstructive pulmonary disease, diabetes complications and hypertension. We used small areas, utilisation-based hospital service areas (HSAs), and administrative districts (Cantons) as geographic zones. The outcomes of interest were age and sex standardised rates of potentially avoidable hospitalisations for ACSCs in adults (> 15 years). Our inferential analyses used linear mixed models with Gaussian distribution. Results We identified 46,479 hospitalisations for ACSC, or 4.3% of all hospitalisations. Most of these occurred in the elderly population for congestive heart failure and COPD. The median rate of potentially avoidable hospitalisation for ACSC was 527 (IQR 432-620) per 100.000 inhabitants. We found substantial regional variation for HSAs and administrative districts as well as disease-specific regional patterns. Conclusions Differences in continuity of care might be key drivers for regional variation of potentially avoidable hospitalisations for ACSCs. These results provide a new perspective on the functioning of primary care structures in Switzerland and call for novel approaches in effective primary care delivery.